The Africans: A triple heritage : Nature of the Continent - Mazrui, Ali AlAmin (The Annnenberg/CPB Collection, 1986)
Examines Africa as the birthplace of humankind and discusses the impact of geography on African history, including the role of the Nile in the origin of civilization and the introduction of Islam to Africa through its Arabic borders. Also known as: Anatomy of a continent. Closed captioned for the hearing impaired. Target audience: General.